SPINAL CORD INJURIES AND THEIR RECOVERY: WHERE DO THE LIMITS OF NEUROSURGERY END? - Abdukhalilova Oygul (Journals Park Publishing, 2025)
This book illuminates the complex aspects of spinal cord injuries (SCIs) and their treatment. It elaborates on the pathophysiology of SCIs (primary and secondary injuries), diagnostics (CT, MRI), and both conservative and surgical approaches. The book analyzes the current limitations of neurosurgery, particularly the difficulty of nerve regeneration and the obstacles posed by glial scars. Furthermore, innovative treatment methods such as stem cell therapy, gene therapy, biomaterials, and neurotechnologies are discussed, emphasizing the importance of future research and combined therapies. The work provides comprehensive information on the challenges in treating SCIs and the scientific pursuits aimed at achieving complete recovery.
Keywords: Spinal Cord Injuries (SCI), Neurosurgery, Pathophysiology, Glial Scars, Nerve Regeneration, Stem Cell Therapy, Gene Therapy, Biomaterials, Neurotechnologies, Rehabilitation.